BIOTECHNOLOGICAL PRODUCTION OF PLANT INOCULANTS BASED ON NITROGEN-FIXING BACTERIA - Pajčin, Ivana S.; Vlajkov, Vanja; Dodić, Jelena; Jokić, Aleksandar; Grahovac, Jovana (Journal on Processing and Energy in Agriculture, 2021)
Nitrogen is one of the essential elements for plant growth and development in terms of DNA and protein synthesis. Its main reservoir in the nature is the atmosphere; however, inert molecular nitrogen present in the air isn’t suitable nitrogen form for plants’ nutrition. Therefore it has to be chemically transformed to NH4+ or NO3- ion by the process known as biological nitrogen fixation. Nitrogen fixation is carried-out by free-living or symbiotic nitrogen-fixing prokaryotes (diazotrophs), including bacteria, archaea and cyanobacteria. In order to be used as plant inoculants for nitrogen fixation, biomass of these prokaryotes must be produced and formulated appropriately through different biotechnological processes. The aim of this study is to summarize the main aspects of biotechnological production of plant inoculants based on nitrogen-fixing bacteria in terms of upstream processing, cultivation and downstream processing, with a special emphasis to cultivation media composition, cultivation conditions, biomass separation and formulation techniques.
Keywords: biological nitrogen fixation; upstream; cultivation; downstream; biomass; formulation